2017
DOI: 10.1159/000478646
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Inflammatory Protein-2 in High Mobility Group Box 1 Secretion of Macrophage Cells Exposed to Lipopolysaccharide

Abstract: Background/Aims: Macrophage inflammatory protein-2 (MIP-2), a type of leukocyte chemokine, is primarily produced by macrophages, and levels increase significantly in early inflammation. However, the precise biological functions and mechanisms of MIP-2 in the development of inflammation remain unclear. The purposes of the present study were to investigate the role of MIP-2 in inflammation induced by lipopolysaccharide (LPS) in vitro and to determine the possibility of blocking the high mobility group box 1 (HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Recent studies have suggested that it exhibits a pronounced proinflammatory effect in the inflammatory response [ 7 ], which is involved in the process of development of sepsis, as well as the important inflammatory mediators for the late period in the lethal effects of LPS [ 8 ]. HMGB1 appears to activate macrophages leading to the secretion of multiple cytokines, which in turn cause extensive inflammatory responses, including intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and nitric oxide [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that it exhibits a pronounced proinflammatory effect in the inflammatory response [ 7 ], which is involved in the process of development of sepsis, as well as the important inflammatory mediators for the late period in the lethal effects of LPS [ 8 ]. HMGB1 appears to activate macrophages leading to the secretion of multiple cytokines, which in turn cause extensive inflammatory responses, including intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and nitric oxide [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that propofol can block endotoxin-induced monocyte-macrophages to produce various inflammatory factors [ 3 , 5 , 9 ]. LPS stimulation can induce HMGB1 release from mouse macrophages, however, propofol can inhibit this process leading to downregulation of HMGB1 mRNA and also block the activation of nuclear transcription factor-κB (NF-κB) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we chose LPS to induce an inflammation model in piglets. Previous research showed that LPS could induce HMGB1 production in BEAS-2B cells and trigger acute lung injury [ 57 ], and that it stimulated HMGB1 secretion in RAW264.7 cells [ 58 ]. Consistent with previous research, our results indicated that LPS also could trigger HMGB1 production in the piglet.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of HMGB1 to TLR2/TLR4 receptors activates multiple pathways ( Fig. 1 ), including myeloid differentiation factor 88 (MyD88) dependent and independent pathways ( Kang et al, 2014 ),MAPKs( Chaochao et al, 2017 ), nod-like receptor protein 3 (NLRP3) ( Kim et al, 2018 ), ultimately leading to the inflammatory genes’ expression and microglial activation ( Yang et al, 2015b ).…”
Section: The Possible Mechanism Underlying Hmgb1-induced Depressionmentioning
confidence: 99%